Modeling dynamical ejecta from binary neutron star mergers and implications for electromagnetic counterparts. (26th April 2017) - Dietrich, Tim; Ujevic, Maximiliano
Abstract: In addition to the emission of gravitational waves (GWs) the coalescence and merger of two neutron stars will produce a variety of electromagnetic (EM) signals. In this work we combine a set of 172 numerical relativity simulations performed by different groups employing different numerical codes and we present fits for the mass, kinetic energy, and the velocities of the dynamical ejected material. The obtained fits have residual errors of the same order as the uncertainties of the numerical relativity simulations. Additionally, we comment on the geometry and composition of the ejecta and discuss the influence of the stars' individual rotation. The derived fits can be used to approximate the main properties of kilonovae (macronovae) and radio flares. Furthermore, in cases for which the ejecta mass is known with high precision, we present a way to determine the luminosity and lightcurve of the kilonovae. Overall, the correlation between the binary parameters and the EM signals allows one in the case of a GW detection to approximate possible EM counterparts when first estimates of the masses are available. After a possible kilonovae observation our results could also be used to restrict the region of the parameter space which has to be covered by numerical relativity simulations.